Perbedaan Tingkat Kecemasan Antara Remaja Yang Telah Mengalami Menarche Dan Belum Mengalami Menarche Di SD Muhammadiyah 1 Surakarta - AMALIA, AFDELINA RIZKY (2016)
Background : Menarche is development of reproductive system in female can result in change of emotional condition for girls in sexual maturity proces, including anxiety. The development pattern of puberty, sign by menarche condition. It will change psychology pattern of girl adolescent, then it also will different with adolescent who doesn't menarche yet. Objective : To determined the differences between anxiety of a teen who has menarche and hasn't menarche yet Methods : Using observasional analytic cross-sectional approach. The number of sample were 35 menarche and 35 non menarche in SD Muhammadiyah 1 Surakarta and being selected by purposive sampling technique. Data collection was done by fill out the form biodata, informed consent, LMMPI questionnare, and TMAS questionnaire. Data were analyzed by chi square test to attempt the hypothesis. Result : Result showed teen who has menarche that 29 people (33%) feel more anxiety than teen who hasn't menarche that 15 people (12%). After the chi square test, significancy value 0,001 (P<0,05). Conclusion : There is a difference in the level of anxiety among teen who has menarche and hasn't menarche yet in SD Muhammadiyah 1 Surakarta, where teen has menarche is more anxious than hasn't menarche yet.